TRANSFORMASI DIGITAL GURU BIMBEL DLL COURSE MELALUI PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN BAAMBOOZLE - Agus Darmawan; Syamsiah Syamsiah; Een Juhriah; Dewi Leyla Rahmah (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of digital technology has had a significant impact on the world of education, including tutoring institutions. Teachers are required to utilize technology as an innovative and interactive learning medium. However, some teachers are still not optimal in using digital learning media in the teaching and learning process. This Community Service (PKM) activity aims to improve the digital competence of DLL Course tutoring teachers through the development of interactive learning media using Baamboozle. The activity implementation method is carried out through the stages of observation, socialization, training, direct practice, and evaluation. Participants are teachers at the DLL Course tutoring institution. The results of the activity show an increase in teachers' understanding and skills in creating educational game-based learning media using Baamboozle. Teachers are able to develop interactive quizzes, educational games, and learning activities that are more engaging for students. This activity has a positive impact on the digital transformation of learning in the DLL Course tutoring environment. ABSTRAK Perkembangan teknologi digital memberikan dampak besar terhadap dunia pendidikan, termasuk pada lembaga bimbingan belajar. Guru dituntut untuk mampu memanfaatkan teknologi sebagai media pembelajaran yang inovatif dan interaktif. Namun, masih terdapat guru yang belum optimal dalam menggunakan media pembelajaran digital dalam proses belajar mengajar. Kegiatan Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan kompetensi digital guru Bimbel DLL Course melalui pengembangan media pembelajaran interaktif menggunakan Baamboozle. Metode pelaksanaan kegiatan dilakukan melalui tahapan observasi, sosialisasi, pelatihan, praktik langsung, dan evaluasi. Peserta kegiatan merupakan guru pada lembaga Bimbel DLL Course. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan keterampilan guru dalam membuat media pembelajaran berbasis game edukasi menggunakan Baamboozle. Guru mampu mengembangkan kuis interaktif, permainan edukatif, dan aktivitas pembelajaran yang lebih menarik bagi peserta didik. Kegiatan ini memberikan dampak positif terhadap transformasi digital pembelajaran di lingkungan Bimbel DLL Course..